Kesantunan dalam Bahasa Melayu Ternate - Fida Febriningsih; Mujahid Taha (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2018)
Nowadays, language politeness seems to be ignored in communication. It happens not only in Indonesia language usage, but also in vernicular usage. Ternate Malay Language is one of languages that spoken in North Maluku. This study aims to describe the language politeness in Ternate Malay Language, and to explain specifically about the principle of politeness and speech form based on a politeness measurement scale. This study uses a description method with three stages, namely the stage of providing data, data analysis, and presenting the results of data analysis. The results of the study found that the principle of speech politeness was divided into tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, dan simpathy maxim, while the forms of speech based on language politeness measuring scale was divided into optionality scale, loss and profit (cost-benefit scale), non-sustainability (indirectness scale), authority scale (authority scale), and social distance scale (social distance).